Carbon Black Particle Exhibits Size Dependent Toxicity in Human Monocytes - Devashri Sahu; G. M. Kannan; R. Vijayaraghavan (International Journal of Inflammation)
Increased levels of particulate air pollution are associated with increased respiratory and cardiovascular mortality and morbidity. Some epidemiologic and toxicological researches suggest ultrafine particles (<100 nm) to be more harmful per unit mass than larger particles. In the present study, the effect of particle size (nano and micro) of carbon black (CB) particle on viability, phagocytosis, cytokine induction, and DNA damage in human monocytes, THP-1 cells, was analysed. The cells were incubated with nanosize (~50 nm) and micron (~500 nm) size of CB particles in a concentration range of 50–800 µg/mL. The parameters like MTT assay, phagocytosis assay, ELISA, gene expression, and DNA analysis were studied. Exposure to nano- and micron-sized CB particles showed size- and concentration dependent decrease in cell viability and significant increase in proinflammatory cytokines IL-1β, TNF-α and IL-6 as well as chemokine IL-8 release. Gene expression study showed upregulation of monocyte chemoattractant protein-1 gene while cyclooxygenase-2 gene remained unaffected. Nano CB particles altered the phagocytic capacity of monocytes although micron CB had no significant effect. CB particles did not show any significant effect on DNA of monocytes. The investigations indicate that CB particles in nanosize exhibit higher propensity of inducing cytotoxicity, inflammation, and altered phagocytosis in human monocytes than their micron size.